2017
DOI: 10.3389/fimmu.2017.01877
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Probiotic Compound Improves Reproductive Performance of Porcine Epidemic Diarrhea Virus-Infected Sows Reared in a Japanese Commercial Swine Farm under Vaccine Control Condition

Abstract: Lactogenic immunity transferred to piglets after inoculation of a live vaccine to pregnant sows was proved limited to control porcine epidemic diarrhea (PED). Hence, here we evaluated the efficacy of administration of a probiotic compound containing Bacillus mesentericus, Clostridium butyricum, and Enterococcus faecalis together with a commercial live-attenuated PED vaccine (Nisseiken PED Live Vaccine, Nisseiken, Tokyo, Japan) to improve the health and reproductive performance of PED-infected sows. Twenty preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 40 publications
0
19
0
1
Order By: Relevance
“…In our previous study, we showed that the probiotic compound improved the reproductive performance of sows vaccinated against PED by stimulating PED‐specific antibodies (Inatomi et al., ). In the present study, we supplemented this probiotic compound to unvaccinated sows.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…In our previous study, we showed that the probiotic compound improved the reproductive performance of sows vaccinated against PED by stimulating PED‐specific antibodies (Inatomi et al., ). In the present study, we supplemented this probiotic compound to unvaccinated sows.…”
Section: Discussionmentioning
confidence: 98%
“…Previously, we reported that a probiotic compound with peptide‐zinc complexes named BIO‐THREE PZ, containing live bacteria Bacillus mesentericus , Clostridium butyricum and Enterococcus faecalis , improved the reproductive performance of sows and prevented post‐weaning diarrhea in piglets (Hayakawa, Masuda, Kurosawa, & Tsukahara, ). More recently, we also showed that the above probiotic compound improved the reproductive performance of sows vaccinated against PED and reduced mortality in suckling piglets (Inatomi, Amatatsu, Romero‐Pérez, Inoue, & Tsukahara, ).…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Thus, substitutes for antibiotics, which can prevent infections at the weaning stage, are 53 urgently required. Evidence suggesting that probiotics, as alternatives to antibiotics, have positive 54 effects in controlling infection and promoting growth mainly due to the competitive exclusion of 55 pathogenic bacteria, has emerged (Inatomi et al 2017; Kim et al 2018).…”
Section: Introductionmentioning
confidence: 99%